Abnormal Neurodevelopmental Outcomes are Common in Children with Transient Congenital Hyperinsulinism - Avatapalle, Bindu H.; Banerjee, Indraneel (Indi); Shah, Sajni; Pryce, Megan; Nicholson, Jacqueline; Rigby, Lindsey; Caine, Louise; Didi, Mohammed; Skae, Mars; Ehtisham, Sarah; Patel, Leena; Padidela, Raja; et al. (Frontiers in Endocrinology, 2013)
Introduction: Neuroglycopaenia is recognised to be associated with abnormal neurodevelopmental outcomes in 26-44% of children with persistent congenital hyperinsulinism (P-CHI). The prevalence of abnormal neurodevelopment in transient CHI (T-CHI) is not known. We have aimed to investigate abnormal neurodevelopment and associated factors in T-CHI and P-CHI. Materials and Methods: A cohort of children with CHI (n=67, age 2.5-5 years) was assessed at follow up review and noted to have normal or abnormal (mild or severe) neurodevelopmental outcomes for the domains of speech and language, motor and vision. Children were classified as P-CHI (n=33), if they had undergone surgery or remained on medical therapy, or T-CHI (n=34), if medical treatment for hypoglycaemia was stopped. Results: Overall, abnormal neurodevelopment was present in 26 (39%) children with CHI, of whom 18 (69%) were severe. Importantly, the incidence of abnormal neurodevelopment in T-CHI was similar to that in P-CHI (30% v 47% respectively, p=0.16). The prevalence of severe abnormal neurodevelopment in speech, motor and vision domains was similar in both T-CHI and P-CHI children. For this cohort, we found that the severity of disease (based upon maximal diazoxide dose, [odds ratio (95% confidence intervals) 1.3 (1.1;1.5), p=0.03] and early presentation of CHI <7 days following birth [5.9 (1.3;27.8), p=0.02] were significantly associated with abnormal neurodevelopment. There was no significant association with gender, genotype or the histopathological basis of CHI. Conclusions: Abnormal neurodevelopment was evident in one third of children with both T-CHI and P-CHI, early presentation and severe CHI being risk factors. Early recognition and rapid correction of hypoglycaemia are advocated to avoid abnormal neurodevelopment in children with CHI.